2008
DOI: 10.4049/jimmunol.181.1.566
|View full text |Cite
|
Sign up to set email alerts
|

IFN-α/β Signaling Is Required for Polarization of Cytokine Responses toward a Protective Type 1 Pattern during Experimental Cryptococcosis

Abstract: The antiviral activities of type I IFNs have long been established. However, comparatively little is known of their role in defenses against nonviral pathogens. We examined here the effects of type I IFNs on host resistance against the model pathogenic yeast Cryptococcus neoformans. After intratracheal or i.v. challenge with this fungus, most mice lacking either the IFN-α/β receptor (IFN-α/βR) or IFN-β died from unrestrained pneumonia and encephalitis, while all wild-type controls survived. The pulmonary immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
39
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 45 publications
6
39
0
Order By: Relevance
“…Little is known of the ability of fungi to induce type I IFNs and of the in vivo role of these cytokines during fungal infections. We have recently found that, in the absence of type I IFN signaling, there is a polarization toward a type 2, detrimental, cytokine response during infection with the pathogenic yeast C. neoformans [15]. However, IFN responses induced by this pathogen were barely detectable in vitro and occurred in a very restricted range of MOIs.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Little is known of the ability of fungi to induce type I IFNs and of the in vivo role of these cytokines during fungal infections. We have recently found that, in the absence of type I IFN signaling, there is a polarization toward a type 2, detrimental, cytokine response during infection with the pathogenic yeast C. neoformans [15]. However, IFN responses induced by this pathogen were barely detectable in vitro and occurred in a very restricted range of MOIs.…”
Section: Discussionmentioning
confidence: 99%
“…www.eji-journal.eu pathophysiologic manifestations and risk of death [15,32]. Thus, it is possible that the contribution of TLR9 to host defenses against C. albicans can be evidenced only under experimental conditions associated with mild, sublethal infection.…”
Section: Ifn-b Primes Cdc For Increased Candidicidal Activitymentioning
confidence: 99%
See 3 more Smart Citations